(untitled) (Research, Society and Development, 2021)
This article was elaborated from a dissertation defended whose research, developed with a qualitative and bibliographic/documentary approach, presented possibilities of identifying, in the classic tales, the mental processes that the child elaborates for the construction of the number. Therefore, becoming a possible relationship between children’s literature and mathematics, in which the first represents pedagogical potentialities for the teaching of the second one, this article aims to discuss the possibility of developing, through classic tales, the guidelines of the Curriculum Common National Base - BNCC - regarding to the construction of the number in kindergarten stage. In order to achieve this goal, the article was divided into three parts: in the first one, some contributions of literature to the teaching of Mathematics are pointed out; in the second, the text discusses how the process of number construction happens and, in the third part, some suggestions of activities are presented, based on children’s classics, to develop the guidelines of the BNCC, as a way to elucidate the discussions. The proposed activities were developed from the story “The Little Thumb” to exemplify pedagogical possibilities and to stimulate the view of the teacher who intends to teach Mathematics using the classic tales. According to the analyses and discussions presented, it is possible to conclude that literature favors the Mathematics learning, since it creates learning contexts, awakening interest and imagination, stimulating communication and providing the development of both mother tongue and mathematical language.